Calagem para manutenção da correção da acidez em solos sob plantio direto - Resende, Hugo Carneiro de (2021)
The no-tillage (NT) system is becoming a common and growing national practice in Brazil since the 1970s. However, it is important emphasize that to achieve high productivity is essential to liming in correct doses to maintain soil acidity. For this, the diversity of specific regional conditions must be considered for the different types of climates, soil, corrective and production system which are factors that interfere in soil mobility of limestone in the soil. In this context, the aimed with the present work to evaluate the effect of different doses of limestone, applied on the surface, with and without incorporation, on the chemical attributes of the soil and on the grain productivity (corn, soybean, and beans). The experiments were installed in four locations, in the off-season of 2019, and evaluated during two agricultural years, using a randomized block design, with four replications. The treatments were composed of five doses of limestone (0, 2, 4, 6 and 9 Mg ha-1) without incorporation and one dose of 8 Mg ha-1 with incorporation through a 32” harrow. In al experimental plots, soil samples were carried out in the layers from 0.00 to 0.10 m; 0.10 to 0.20 m; and from 0.20 to 0.40 m at the end of the summer harvest of each year, in addition the collection of leaves in the first harvest crops and still, the evaluation of three agronomic characters, yield, plant height and weight of a thousand grains. In these experiments it was observed a linear increase of calcium, magnesium, pH (CaCl2) and base saturation, and inverse linear response for the potential acidity (H+A) in the topsoil with increasing doses. In other hand, for the lower layers, was observed a mobility difference of the corrective along the profile for the different areas; and in the area with more sandy textured soil, there was a linear response in the increase of calcium and magnesium and the pH values in the layer from 0.2 to 0.4 m after 22 months. As for the micronutrients, there was no change in the availability of soil contents and leaf concentration in the evaluated cultures. In the first year of installation of the experiments, there was no response in crop productivity. In the summer harvest of the second year, the productivity was increasing and linear only one of the locations. The applications of limestone with incorporation has the fastest capacity to change the chemical attributes of the soil in the subsurface, but this gain does not reflect the increase in productivity.